Study of Prevalence of Concha Bullosa, Nasal Septal Deviation and Sinusitis based on CT Findings (Bangladesh Journal of Otorhinolaryngology, 2020)
The anatomical variations and pathological conditions of the sinonasal area can be easily identified using computed tomography (CT) scan. The study was done to observe the prevalence of concha bullosa (CB) and nasal septal deviation (DNS) in sinusitis patients. 135 CT scan of nose and paranasal (PNS) sinuses were taken and reviewed retrospectively for the presence of concha bullosa, nasal septal deviation and sinusitis in the department of Otolaryngology, Head and Neck Surgery, Border Guard Hospital, Dhaka from March 2019 to January 2020. Out of 135 patients, CT scan of nose and PNS revealed 74.81% patients exhibited some sinus disease, 68.14% nasal septal deviation and 42.22% had concha bullosa. In this study, we have done a retrospective analysis of the CT scan of PNS in order to assess the prevalence CB, DNS and sinusitis.Bangladesh J Otorhinolaryngol; April 2020; 26(1): 18-23